Experience of diabetes patients in preventing its complications - Hisni, Dayan; Asri Nurani, Intan (Nursing and Health Sciences Journal (NHSJ), 2025)
It is necessary to explore the experience of diabetes patients in preventing its complications since Indonesia has many cultural beliefs and practices that influence the prevention of DM complications. A limited number of studies have discussed it. The study aimed to explore the experiences of diabetes patients in preventing its complications. A descriptive qualitative study was conducted in Indonesia between December 2022 and April 2023. Fifteen participants with DM were included. Purposive sampling was used, and data were collected through in-depth interviews, observations, and the writing of field notes. The data were analyzed by thematic analysis using NVivo 12 software. Four themes emerged from the data analysis: (1) inadequate self-care practice related to misconception about DM and its complications; (2) self-awareness, intention, and motivation as basic to change the behaviors; (3) optimal holistic support is needed from family and health workers; (4) inadequate of education program provided by health workers to prevent DM complications. This is the first study to display that cultural beliefs and knowledge strongly influenced the experience of preventing DM complications. Internal and external environments also contributed to the experience of preventing DM complications. This study offers new insights for nurses in Indonesia and will assist them in designing a nursing intervention involving cultural aspects for diabetic patients.